Mentor-Mentee Relationship: 12 Suggestions from English Mentors to Mentees - Dilveen Abdulstar Sadiq (International Journal of Social Sciences & Educational Studies, 2023)
A wealth of research has been carried out on the effects of mentorship programs in EFL and ESL settings. Mentors have been regarded as the source of knowledge and experience to train mentees. Nearly all countries have allocated a certain amount of time and money for the betterment of English mentorship programs, so the mentees will have ample opportunity to improve their professional conduct in educational institutions. In this study, the concise suggestions of 12 English mentors who have pursued a long career in education through numerous countries were examined. This qualitative study lasted 8 weeks, and the data were collected by in-depth one-on-one interviews which were transcribed and classified through MAXQDA software program. The results demonstrated significant points to consider for less experienced teachers who want to have a promising career in education. The mentors` ideas were categorized under 12 headings to assist less experienced teachers on the way of being a professional and committed teacher. Analyzed data can have some implications for future English mentorship programs and educational institutions on a global scale.